Graphene-based heating coating, preparation method and application of graphene-based heating coating in heating electric appliance
By using hyperbranched polyolefin-acryloyl-POSS copolymers in graphene-modified bismuth telluride nanoribbons in graphene-based heating coatings, the shortcomings of existing coatings in electrothermal properties and adhesion are solved, and efficient and stable electrothermal conversion and long-term stability are achieved.
Patent Information
- Application Number
- CN202510357912.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-25
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2045-03-25
AI Technical Summary
The existing graphene-based heating coatings have shortcomings in terms of electric heating properties and adhesion, resulting in low electric heating efficiency, poor uniformity and easy peeling or cracking during long-term use.
The dispersion, interface bonding and electrothermal properties of the coating are improved by using hyperbranched polyolefin-acryloyl-POSS copolymer functionalized graphene oxide and aminosilane-modified bismuth telluride nanoribbons.
It significantly improves the conductivity, adhesion and uniformity of graphene-based heating coatings, optimizes the electric heat conversion efficiency and stability, and is suitable for the fields of efficient heating and intelligent thermal management.
Smart Images

Figure CN119899577A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of electric heating materials, and in particular to a graphene-based heating coating, a preparation method thereof, and an application thereof in heating appliances. Background Art
[0002] In modern intelligent heating equipment and industrial thermal management systems, efficient and stable heating elements play a vital role in improving energy utilization efficiency, optimizing equipment performance and extending service life. Graphene, as a two-dimensional carbon material with excellent electrical and thermal conductivity, shows great potential in applications such as flexible heating films, electric heating plates, and intelligent temperature control devices. However, in order to meet the actual application needs of heating appliances, the heating coating not only needs to have efficient electrothermal conversion performance, that is, to achieve uniform and rapid temperature response at a lower voltage, but also needs to have excellent adhesion to ensure that the coating exists stably on different substrate surfaces (such as metal, ceramic or polymer substrates) for a long time without peeling or cracking. In addition, the coating must also have good high temperature resistance and environmental stability to adapt to complex working environments, such as long-term reliable operation under high temperature, high humidity or frequent thermal cycle conditions. Therefore, the development of a graphene-based heating coating with high electrothermal conversion efficiency, excellent adhesion and long-term environmental stability can not only improve the overall performance of the heating element, but also broaden its application range in smart homes, healthcare, aerospace and industrial automation, which is of great significance to promote the development of efficient thermal management technology.
[0003] At present, the research on graphene-based heating coatings has made some progress, but there are still deficiencies in electrothermal performance and adhesion. For example, the Chinese patent with publication number CN112920704B discloses an electric heating coating paint, an electric heating skin and an anti-ice and snow system. The coating realizes electrothermal conversion through the excellent conductivity of graphene. However, its electrothermal efficiency is low, and the uniformity and thermal response speed of the coating still need to be improved, resulting in local overheating or uneven heating. In addition, due to the lack of effective interface bonding between graphene and most substrates, the coating is prone to peeling, cracking or adhesion loss during long-term use, especially under high temperature or thermal cycle conditions. The main reason for these deficiencies is that the dispersibility of graphene in the solvent system is limited, resulting in an uneven internal structure of the coating. At the same time, the existing binder or functionalization means cannot effectively enhance the chemical bonding between graphene and the substrate, making the mechanical stability of the coating poor. Therefore, how to optimize the dispersion state of graphene, improve the electrothermal conversion efficiency of the coating and enhance the interface bonding force have become key issues to be solved in the current research on graphene-based heating coatings. Summary of the invention
[0004] (1) Technical issues solved The purpose of the present invention is to provide a graphene-based heating coating and a preparation method and application in heating appliances, so as to solve the problem that the current graphene-based heating coating has insufficient electrical and thermal performance and adhesion performance.
[0005] (2) Technical solution In order to achieve the above object, the present invention provides the following technical solutions: A graphene-based heating coating is prepared from the following raw materials in parts by weight: 3-12 parts of functionalized graphene, 2.5-4.5 parts of surface-modified bismuth telluride nanobelts, 2-8 parts of polyaniline, 12-35 parts of bisphenol A epoxy acrylate, 5-15 parts of polyurethane acrylate, 0.5-1.5 parts of benzoin diethyl ether, 0.5-2.0 parts of BYK-220S dispersant, 0.3-0.8 parts of HY-F-3777 fluorocarbon modified leveling agent, 1.0-2.5 parts of silane coupling agent kh560, 0.2-0.5 parts of silicone emulsion defoamer, and 25-40 parts of propylene glycol methyl ether acetate / N-methylpyrrolidone mixed solvent; The functionalized graphene is prepared by mixing a hyperbranched polyolefin-acryl-POSS copolymer and graphene oxide in a chloroform solvent, and then subjected to ultrasonic stripping, centrifugal separation, vacuum filtration, gradient washing and vacuum drying. The hyperbranched polyolefin-acryl-POSS copolymer is prepared by catalytic polymerization, solvent precipitation, suction filtration and vacuum drying of acrylic-cage polysilsesquioxane, 1,4-butanediol diacrylate and anhydrous dichloromethane in a Schlenk reaction system; The surface modified bismuth telluride nanobelt is prepared by ultrasonically dispersing the bismuth telluride nanobelt in deionized water, adding aminopropyltriethoxysilane for surface modification, and then subjecting the nanobelt to magnetic stirring, centrifugal separation, deionized water washing and vacuum drying.
[0006] Further, the preparation method of the functionalized graphene is as follows: in parts by weight, a hyperbranched polyolefin-acryl-POSS copolymer and graphene oxide are used as raw materials, mixed in a mass ratio of 1: (4-6) and added to 80-100 mL of chloroform solvent to form a mixed system, the mixed system is placed in an ultrasonic treatment device, the ultrasonic power is controlled to be 280-320 W, the treatment time is 25-35 min, and the treatment temperature is maintained at 20-30 ° C, then the mixed system after ultrasonic treatment is transferred to a centrifuge, centrifuged at a speed of 3800-6500 rpm for 40-50 min, the unpeeled aggregates are removed, the supernatant is collected to obtain a graphene primary dispersion, the graphene primary dispersion is vacuum filtered through a polytetrafluoroethylene filter membrane with a pore size of 90-110 nm, and the sediment on the surface of the filter membrane is gradient washed with a chloroform solvent, 45-55 mL of solvent is added each time and the supernatant is centrifuged at 300-500 The mixture was washed at a stirring rate of rpm for 3 to 6 min, and the washing was repeated 3 to 5 times. The purified functionalized graphene powder was dried in a vacuum environment at 35 to 65 °C for 10 to 26 h to obtain functionalized graphene.
[0007] Further, the preparation method of the hyperbranched polyolefin-acryl-POSS copolymer is as follows: by weight, 100 parts of acrylic-cage polysilsesquioxane, 12.0-16.0 parts of 1,4-butanediol diacrylate and 90-110 parts of anhydrous dichloromethane are added to a Schlenk reaction bottle, the system temperature is controlled to be 25-35° C., and the mixture is mixed at a stirring rate of 300-500 rpm for 30-40 min to form a homogeneous solution, then 2.2-2.8 parts of α-diimide palladium by weight are dissolved in 40-60 parts by weight of anhydrous dichloromethane, and the homogeneous solution is injected at a rate of 0.5-1.0 mL / min through a syringe pump, and the ethylene pressure is maintained at 0.08-0.12 MPa, continuously stir and polymerize at 28-32°C for 22-26h. After the reaction, nitrogen is used to purge and remove the solvent to obtain a preliminary product, which is then added with 220-280 parts of tetrahydrofuran to dissolve, and 750-1250 parts of methanol are added dropwise to precipitate. After suction filtration, the filter cake is washed 2-3 times with 250-500 parts of methanol, the product is redissolved in 150-250 parts of tetrahydrofuran, and 500-1000 parts of acetone are added to perform secondary precipitation. The product is vacuum dried at 20-30°C for 70-74h to obtain a hyperbranched polyolefin-acryloyl-POSS copolymer.
[0008] The present invention adopts the design of hyperbranched polyolefin-acryl-POSS copolymer functionalized graphene oxide to be mainly used for enhancing the dispersion stability, interfacial bonding force and electrothermal performance of graphene-based materials. By introducing hyperbranched polyolefin-acryl-POSS copolymer, its unique hyperbranched structure provides abundant functional groups, and can form strong interaction with graphene oxide, thereby effectively improving the dispersibility of graphene in solvent system, and promoting its uniformity in composite system. In addition, the presence of acryl-POSS part gives material higher chemical stability and thermal stability, so that functionalized graphene can still maintain excellent electrical conductivity under high temperature environment. By steps such as ultrasonic stripping, centrifugation and gradient washing, unreacted aggregates and impurities can be efficiently removed, ensuring that the obtained functionalized graphene has high purity and excellent lamellar structure, thereby further optimizing its electrothermal conversion efficiency. During the preparation process, the synthesis of hyperbranched polyolefin-acryl-POSS copolymer adopts Schlenk reaction system, and a hyperbranched polymer with good solubility is obtained through steps such as ethylene polymerization and solvent precipitation. The polymer can effectively combine with graphene oxide and promote its peeling, increase the interlayer spacing and specific surface area of graphene, thereby enhancing its interfacial compatibility in the coating system. In addition, chloroform as a solvent can provide a suitable polar environment, which is conducive to the uniform adsorption of hyperbranched polyolefin-acryl-POSS copolymer on the surface of graphene oxide, and realizes effective modification of graphene. Finally, the residual solvent is removed by vacuum drying process to obtain stable functionalized graphene powder. This material not only has excellent dispersion stability and interfacial bonding force, but also can effectively improve the conductive network structure of graphene in subsequent coating applications, and improve the electrothermal conversion efficiency and long-term stability of the overall coating.
[0009] Furthermore, the preparation method of the surface modified bismuth telluride nanobelt is as follows: weigh 100 parts of bismuth telluride nanobelt by weight, add 200-500 parts of deionized water, and disperse for 30-60 minutes under the conditions of ultrasonic power of 100-300 W and frequency of 35-40 kHz to form a uniform suspension; add 5-20 parts of -aminopropyltriethoxysilane to the suspension, stir for 1-3 hours at a magnetic stirring rate of 300-400 rpm, and after the reaction is completed, centrifuge the suspension at 3000-8000 rpm for 10-20 minutes for solid-liquid separation, and wash the separated solid with 50-100 parts of deionized water for 2-3 times, each washing with a stirring rate of 200-400 rpm for 5-10 minutes; finally, place the solid in a vacuum drying oven at a temperature of 60-100°C and a temperature of -0.08--0.10 MPa vacuum conditions for 6 to 12 hours to obtain surface-modified bismuth telluride nanobelts.
[0010] Furthermore, the preparation method of the bismuth telluride nanobelt is as follows: 9.5-10.5 mmol bismuth chloride dihydrate, 14.5-15.5 mmol tellurium powder, 78-82 mmol potassium hydroxide and 29-31 mmol potassium borohydride are mixed and transferred to a polytetrafluoroethylene-lined high-pressure reactor, and N,N-dimethylformamide is injected to 85-95wt.% of the volume of the reactor to form a precursor suspension; the sealed reactor is placed in a programmable oven, heated to 100-180°C at a heating rate of 2-5°C / min and kept at a constant temperature for 10-20h, and then naturally cooled to 25-35°C at a rate of 0.5-2.0°C / min; after opening the reactor, the reaction mixture is filtered through a Buchner funnel at a vacuum degree of -0.08-0.10 MPa, and washed repeatedly with 50-100 mL of deionized water for 3-5 times, and then washed with 30-50 mL of deionized water for 3-5 times. mL of anhydrous ethanol was repeatedly washed 2 to 3 times; finally, the product was dried at 75 to 85°C and -0.08 to -0.10 MPa vacuum for 8 to 12 h to obtain bismuth telluride nanobelts.
[0011] Furthermore, the average width of the bismuth telluride nanoribbons is 20-50 nm, and the average length is 1-10 μm.
[0012] The present invention adopts the design of aminosilane surface modified bismuth telluride nanobelts mainly for enhancing the interface compatibility and dispersion stability of the material. As a functional filler, the excellent thermoelectric properties of bismuth telluride nanobelts make it have extensive potential in electrical conduction and thermal management applications, but its surface activity is low and it is easy to agglomerate, which limits its uniform distribution and interface binding ability in the composite system. Through the introduction of aminopropyltriethoxysilane, a stable organosilane layer can be formed on the surface of bismuth telluride nanobelts, which not only improves the dispersibility of the nanobelts, but also enhances its binding force with the matrix resin or other fillers. During the ultrasonic dispersion process, the bismuth telluride nanobelts form a uniform suspension system in the deionized water medium, and then the physical adsorption and chemical bonding of aminosilane and the surface of the nanobelts are promoted by magnetic stirring to ensure the uniformity and stability of the modified layer. After centrifugation and multiple washings, the unreacted silane and impurities can be effectively removed to improve the purity of the modified material. Finally, residual water and solvent are removed by vacuum drying process, so that the surface modified bismuth telluride nanobelt has good storage stability and application adaptability. In addition, the synthesis of bismuth telluride nanobelt adopts dihydrated bismuth chloride, tellurium powder, potassium hydroxide and potassium borohydride to carry out solvothermal reaction in a high-pressure reactor. The introduction of N, N-dimethylformamide provides a good dissolution environment for the reaction system, which is conducive to the formation and growth of bismuth telluride nanobelt. By optimizing the heating rate and constant temperature reaction time, the size and morphology of the nanobelt can be controlled to ensure its stability in subsequent modification and composite system. After cooling, filtration and multiple washing, the obtained bismuth telluride nanobelt can be further purified and dried under suitable temperature and vacuum conditions to obtain a nanobelt structure with high crystallinity and good dispersibility. Overall, the present invention uses a reasonable synthesis and modification strategy to make the bismuth telluride nanobelt maintain excellent thermoelectric properties while significantly improving its stability in solvents and composite matrices, and enhancing its interface bonding ability with other functional materials, thereby improving the overall performance and practicality of the composite system.
[0013] Furthermore, the propylene glycol methyl ether acetate / N-methyl pyrrolidone mixed solvent is a mixture of propylene glycol methyl ether acetate and N-methyl pyrrolidone in a volume ratio of (30-45): (55-70).
[0014] The present invention also discloses a method for preparing a graphene-based heating coating, comprising the following steps: S1. Add propylene glycol methyl ether acetate / N-methyl pyrrolidone mixed solvent, BYK-220S dispersant and silicone emulsion defoamer into a stirring tank, premix for 10-20 min at a stirring rate of 200-400 rpm, control the system temperature to maintain 25±5°C, then add functionalized graphene and surface-modified bismuth telluride nanoribbons, increase the stirring rate to 800-1200 rpm and continue for 30-60 min to form a primary dispersed slurry; S2. polyaniline, bisphenol A epoxy acrylate and polyurethane acrylate were added to the primary dispersed slurry in sequence, and an ultrasonic probe was used to treat the slurry at a power of 100-300 W and a frequency of 20-40 kHz for 30-60 min, and the viscosity of the slurry was controlled to 2000-4000 mPa·s at room temperature. Silane coupling agent KH560 was added, and the mixture was stirred at a rate of 500-800 rpm for 60-120 min under nitrogen protection to form a uniform composite slurry; S3. Add benzoin diethyl ether and HY-F-3777 fluorocarbon modified leveling agent to the composite slurry, mix at a stirring rate of 300-500 rpm for 20-40 min under light-proof conditions, and filter online through a microfiltration membrane with a pore size of 1-5 μm to remove aggregates to obtain the final coating slurry; S4. Apply the coating slurry on the surface of the substrate, transfer it to a UV curing device, irradiate it at a wavelength of 365 nm and a light intensity of 50~100 mW / cm² for 3~8 minutes, control the substrate temperature at 45~60℃, and then post-cure it in a hot air circulation oven at 80~100℃ for 10~30 minutes to form a graphene-based heating coating.
[0015] The invention also discloses an application of a graphene-based heating coating in a heating appliance.
[0016] The present invention adopts the design of the preparation process combining multi-component synergistic dispersion and ultraviolet curing, which is mainly used to enhance the conductivity, adhesion and uniformity of the graphene-based heating coating. By introducing the propylene glycol methyl ether acetate / N-methyl pyrrolidone mixed solvent, a good dissolution environment is provided for the coating system, ensuring the uniform dispersion of functionalized graphene and surface-modified bismuth telluride nanobelts, and further reducing the risk of filler agglomeration under the action of BYK-220S dispersant, and improving the dispersion stability. At the same time, the addition of the silicone emulsion defoamer effectively controls the bubble content of the system, avoiding bubbles from affecting the film quality during the coating curing process. By gradually increasing the stirring rate, the functionalized graphene and surface-modified bismuth telluride nanobelts are fully dispersed under a high shear environment to form a stable primary dispersion slurry. In the subsequent steps, polyaniline, bisphenol A epoxy acrylate and polyurethane acrylate are added in sequence, and the uniform mixing of each component is promoted by ultrasonic probe treatment, and the slurry viscosity is optimized to ensure the rheological properties and film quality of the final coating. In addition, the introduction of silane coupling agent KH560 enhances the interfacial bonding force between the filler and the polymer matrix, and improves the overall mechanical stability and adhesion performance of the coating. In a light-proof environment, the addition of benzoin diethyl ether and HY-F-3777 fluorocarbon modified leveling agent further optimizes the leveling of the slurry, allowing the coating to form a uniform and smooth film layer on the surface of the substrate, and removes possible aggregates through microfiltration membrane filtration to ensure the uniformity and surface quality of the final coating. Finally, a UV curing combined with hot air post-curing process is adopted. Through the irradiation of 365 nm wavelength ultraviolet light, the photosensitive initiator triggers the curing reaction and quickly forms a stable coating. At the same time, the substrate temperature is controlled to adapt to different application requirements. Further curing is carried out in a hot air environment of 80~100℃ to improve the crosslinking density and heat resistance stability of the coating, thereby ensuring the long-term stability and efficient electrothermal conversion capability of the graphene-based heating coating in heating appliances. In general, the present invention achieves a comprehensive improvement in the conductivity, adhesion and uniformity of the graphene-based heating coating through multiple means such as solvent optimization, dispersion stabilization, interface enhancement and curing process optimization, providing a high-performance and highly reliable functional coating material for heating electrical appliances.
[0017] (3) Beneficial technical effects 1. The present invention functionalizes graphene oxide by hyperbranched polyolefin-acryl-POSS copolymer, thereby improving the dispersibility, interfacial bonding strength and electrothermal performance of graphene. Compared with the prior art, the uniformity and conductivity of the coating are enhanced, the electrothermal conversion efficiency and stability are optimized, and the coating is suitable for the field of high-efficiency heating coatings and intelligent thermal management.
[0018] 2. The present invention improves the dispersibility and interfacial bonding strength of bismuth telluride nanobelts through aminosilane modification, avoids agglomeration, improves the stability and thermoelectric properties of the composite material, and compared with the prior art, enhances the conductivity and mechanical strength, optimizes the synergistic effect of the components, and is suitable for the field of high-efficiency thermal conductivity and electronic devices.
[0019] 3. The present invention achieves significant improvements in the conductivity, adhesion and uniformity of the graphene-based heating coating by optimizing the solvent system, improving the dispersion of the filler, enhancing the interfacial bonding force and adopting a UV curing process. Compared with the existing technology, it has higher electrothermal conversion efficiency, better mechanical stability and longer service life, meeting the needs of heating appliances for efficient and stable coatings. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 The graphene-based heating coating prepared in Example 1 of the present invention and its infrared spectrum when heated.
[0021] Figure 2 This is the XRD phase analysis spectrum of the surface-modified bismuth telluride nanoribbon prepared in Example 1 of the present invention.
[0022] Figure 3 This is a morphology image of the surface-modified bismuth telluride nanobelt prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0023] To make the purpose, technical solution and advantages of the embodiments of the present invention more clear, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention.
[0024] Example 1
[0025] A graphene-based heating coating is prepared from the following raw materials in parts by weight: 3 parts of functionalized graphene, 2.5 parts of surface-modified bismuth telluride nanoribbons, 2 parts of polyaniline, 12 parts of bisphenol A epoxy acrylate, 5 parts of polyurethane acrylate, 0.5 parts of benzoin diethyl ether, 0.5 parts of BYK-220S dispersant, 0.3 parts of HY-F-3777 fluorocarbon modified leveling agent, 1.0 parts of silane coupling agent kh560, 0.2 parts of silicone emulsion defoamer, and 25 parts of propylene glycol methyl ether acetate / N-methylpyrrolidone mixed solvent.
[0026] The preparation method of functionalized graphene is as follows: in parts by weight, hyperbranched polyolefin-acryl-POSS copolymer and graphene oxide are used as raw materials, mixed in a mass ratio of 1:4 and added into 80 mL of chloroform solvent to form a mixed system, the mixed system is placed in an ultrasonic treatment device, the ultrasonic power is controlled to be 280 W, the treatment time is 25 min, and the treatment temperature is maintained at 20° C., then the mixed system after ultrasonic treatment is transferred to a centrifuge, centrifuged at a speed of 3800 rpm for 40 min, unpeeled aggregates are removed, the supernatant is collected to obtain a graphene primary dispersion, the graphene primary dispersion is vacuum filtered through a polytetrafluoroethylene filter membrane with a pore size of 90 nm, and the sediment on the surface of the filter membrane is gradient washed with a chloroform solvent, 45 mL of solvent is added each time and washed at a stirring rate of 300 rpm for 3 min, the washing is repeated 3 times, and the purified functionalized graphene powder is dried in a vacuum environment at 35° C. for 10 h to obtain functionalized graphene.
[0027] The preparation method of the hyperbranched polyolefin-acryl-POSS copolymer is as follows: by weight, 100 parts of acrylic-cage polysilsesquioxane, 12.0 parts of 1,4-butanediol diacrylate and 90 parts of anhydrous dichloromethane are added to a Schlenk reaction bottle, the system temperature is controlled to be 25° C., and the mixture is mixed at a stirring rate of 300 rpm for 30 min to form a homogeneous solution, then 2.2 parts of α-diimide palladium by weight are dissolved in 40 parts of anhydrous dichloromethane, and the mixture is stirred at 0.5 mL / min by a syringe pump. The homogeneous solution was injected at a rate of n, the ethylene pressure was maintained at 0.08 MPa, and the polymerization was continuously stirred at 28°C for 22 hours. After the reaction was completed, the solvent was removed by purging with nitrogen to obtain a preliminary product, which was then added with 220 parts of tetrahydrofuran to dissolve it, and 750 parts of methanol were added dropwise to precipitate it. After suction filtration, the filter cake was washed twice with 250 parts of methanol, the product was redissolved in 150 parts of tetrahydrofuran, 500 parts of acetone were added to carry out secondary precipitation, and it was vacuum dried at 20°C for 70 hours to obtain a hyperbranched polyolefin-acryloyl-POSS copolymer.
[0028] The preparation method of surface modified bismuth telluride nanobelt is as follows: 100 parts of bismuth telluride nanobelt are weighed by weight, 200 parts of deionized water are added, and a uniform suspension is formed by dispersion for 30 minutes under the conditions of ultrasonic power of 100W and frequency of 35kHz; 5 parts of -aminopropyltriethoxysilane are added to the suspension, and the suspension is stirred for 1 hour at a magnetic stirring rate of 300rpm. After the reaction is completed, the suspension is centrifuged at 3000rpm for 10 minutes for solid-liquid separation, and the separated solid is washed twice with 50 parts of deionized water in turn, and the stirring rate of each washing is 200rpm and the duration is 5 minutes; finally, the solid is placed in a vacuum drying oven, and dried for 6 hours at a temperature of 60°C and a vacuum degree of -0.08MPa to obtain the surface modified bismuth telluride nanobelt.
[0029] The preparation method of bismuth telluride nanobelts is as follows: 9.5mmol bismuth chloride dihydrate, 14.5mmol tellurium powder, 78mmol potassium hydroxide and 29mmol potassium borohydride are mixed and transferred to a polytetrafluoroethylene-lined high-pressure reactor, and N,N-dimethylformamide is injected to 85wt.% of the volume of the reactor to form a precursor suspension; the sealed reactor is placed in a programmable oven, heated to 100℃ at a heating rate of 2℃ / min and kept at a constant temperature for 10h, and then naturally cooled to 25℃ at a rate of 0.5℃ / min; after opening the reactor, the reaction mixture is filtered through a Buchner funnel at a vacuum degree of -0.08MPa, and washed repeatedly with 50mL deionized water for 3 times, and then washed repeatedly with 30mL anhydrous ethanol for 2 times; finally, the product is dried at 75℃ and a vacuum degree of -0.08MPa for 8h to obtain bismuth telluride nanobelts.
[0030] The average width of the bismuth telluride nanoribbons in this embodiment is 20 nm; the average length is 1 μm; The propylene glycol methyl ether acetate / N-methyl pyrrolidone mixed solvent of this embodiment is a mixture of propylene glycol methyl ether acetate and N-methyl pyrrolidone in a volume ratio of 30:70.
[0031] A method for preparing a graphene-based heating coating of this embodiment includes the following steps: S1. Add chloroform / propylene glycol methyl ether acetate mixed solvent, BYK-220S dispersant and silicone emulsion defoamer into a stirring tank, premix for 10 min at a stirring rate of 200 rpm, control the system temperature to maintain 25±5°C, then add functionalized graphene and surface-modified bismuth telluride nanoribbons, increase the stirring rate to 800 rpm and continue for 30 min to form a primary dispersed slurry; S2. polyaniline, bisphenol A epoxy acrylate and polyurethane acrylate were sequentially added to the primary dispersed slurry, and an ultrasonic probe was used to treat the slurry at a power of 100 W and a frequency of 20 kHz for 30 min, and the viscosity of the slurry was controlled to 2000 mPa·s at room temperature. Silane coupling agent KH560 was continuously added, and the mixture was stirred at a rate of 500 rpm for 60 min under nitrogen protection to form a uniform composite slurry; S3. Add benzoin diethyl ether and HY-F-3777 fluorocarbon modified leveling agent to the composite slurry, mix at a stirring rate of 300 rpm for 20 min under light-proof conditions, and filter online through a microfiltration membrane with a pore size of 1 μm to remove aggregates to obtain a final coating slurry; S4. Apply the coating slurry on the surface of the substrate, transfer it to a UV curing device, irradiate it for 3 minutes at a wavelength of 365nm and a light intensity of 50mW / cm², control the substrate temperature at 45℃, and then post-cure it in a hot air circulation oven at 80℃ for 10 minutes to form a graphene-based heating coating.
[0032] Depend on Figure 1 It can be seen that the infrared spectrum of the graphene-based heating coating prepared in Example 1 of the present invention when heated shows that it has an excellent heating effect, which proves that the coating has good thermal response performance. Figure 2 The XRD phase analysis shown indicates that the prepared surface-modified bismuth telluride nanobelts have a clear crystal structure, which is consistent with the target compound, proving the success of the synthesis and the purity of the material. Figure 3 The morphological characteristics of the nanobelt were further demonstrated, indicating that it had good morphological uniformity and nanoscale structure. These results together verified the feasibility and effectiveness of Example 1 of the present invention.
[0033] Example 2
[0034] A graphene-based heating coating is prepared from the following raw materials in parts by weight: 6 parts of functionalized graphene, 3.1 parts of surface-modified bismuth telluride nanoribbons, 4 parts of polyaniline, 19 parts of bisphenol A epoxy acrylate, 8 parts of polyurethane acrylate, 0.8 parts of benzoin diethyl ether, 0.9 parts of BYK-220S dispersant, 0.5 parts of HY-F-3777 fluorocarbon modified leveling agent, 1.5 parts of silane coupling agent kh560, 0.3 parts of organosilicon emulsion defoamer, and 29 parts of propylene glycol methyl ether acetate / N-methylpyrrolidone mixed solvent.
[0035] The preparation method of functionalized graphene is as follows: in parts by weight, hyperbranched polyolefin-acryl-POSS copolymer and graphene oxide are used as raw materials, mixed in a mass ratio of 1:4.6 and added into 86 mL of chloroform solvent to form a mixed system, the mixed system is placed in an ultrasonic treatment device, the ultrasonic power is controlled to be 292 W, the treatment time is 28 min, and the treatment temperature is maintained at 23° C., then the mixed system after ultrasonic treatment is transferred to a centrifuge, centrifuged at a speed of 4610 rpm for 43 min, unpeeled aggregates are removed, the supernatant is collected to obtain a graphene primary dispersion, the graphene primary dispersion is vacuum filtered through a polytetrafluoroethylene filter membrane with a pore size of 96 nm, and the sediment on the surface of the filter membrane is gradient washed with a chloroform solvent, 48 mL of solvent is added each time and washed at a stirring rate of 360 rpm for 4 min, the washing is repeated 3 times, and the purified functionalized graphene powder is dried in a vacuum environment at 44° C. for 15 h to obtain functionalized graphene.
[0036] The preparation method of the hyperbranched polyolefin-acryl-POSS copolymer is as follows: by weight, 100 parts of acrylic-cage polysilsesquioxane, 13.2 parts of 1,4-butanediol diacrylate and 96 parts of anhydrous dichloromethane are added to a Schlenk reaction bottle, the system temperature is controlled to be 28°C, and the mixture is stirred at a stirring rate of 360 rpm for 33 minutes to form a homogeneous solution, then 2.4 parts of α-diimide palladium are dissolved in 46 parts of anhydrous dichloromethane, and the mixture is stirred at 0.6 mL / min via a syringe pump. The homogeneous solution was injected at a rate of n, the ethylene pressure was maintained at 0.09 MPa, and the polymerization was continuously stirred at 29°C for 23 hours. After the reaction, the solvent was removed by purging with nitrogen to obtain a preliminary product, which was then dissolved in 238 parts of tetrahydrofuran, and 900 parts of methanol were added dropwise for precipitation. After filtration, the filter cake was washed twice with 325 parts of methanol, the product was redissolved in 180 parts of tetrahydrofuran, 650 parts of acetone were added for secondary precipitation, and vacuum dried at 23°C for 71 hours to obtain a hyperbranched polyolefin-acryloyl-POSS copolymer.
[0037] The preparation method of surface modified bismuth telluride nanobelt is as follows: 100 parts of bismuth telluride nanobelt are weighed by weight, 290 parts of deionized water are added, and a uniform suspension is formed by dispersing for 39 minutes under the conditions of ultrasonic power of 160W and frequency of 36.5kHz; 9.5 parts of -aminopropyltriethoxysilane are added to the suspension, and the suspension is stirred for 1.6 hours at a magnetic stirring rate of 330rpm. After the reaction is completed, the suspension is centrifuged at 4500rpm for 13 minutes for solid-liquid separation, and the separated solid is washed twice with 65 parts of deionized water in turn, and the stirring rate of each washing is 260rpm and the duration is 6.5 minutes; finally, the solid is placed in a vacuum drying oven and dried for 7.8 hours at a temperature of 72°C and a vacuum degree of -0.086MPa to obtain a surface modified bismuth telluride nanobelt.
[0038] The preparation method of bismuth telluride nanobelts is as follows: 9.8 mmol bismuth chloride dihydrate, 14.8 mmol tellurium powder, 79.2 mmol potassium hydroxide and 29.6 mmol potassium borohydride are mixed and transferred to a polytetrafluoroethylene-lined high-pressure reactor, and N,N-dimethylformamide is injected to 88 wt.% of the volume of the reactor to form a precursor suspension; the sealed reactor is placed in a programmable oven, heated to 124°C at a heating rate of 2.9°C / min and kept at a constant temperature for 13 hours, and then naturally cooled to 28°C at a rate of 0.95°C / min; after opening the reactor, the reaction mixture is filtered through a Buchner funnel at a vacuum degree of -0.086 MPa, and washed repeatedly with 65 mL of deionized water for 3 times, and then washed repeatedly with 36 mL of anhydrous ethanol for 2 times; finally, the product is dried at a temperature of 78°C and a vacuum degree of -0.086 MPa for 9.2 hours to obtain bismuth telluride nanobelts.
[0039] The average width of the bismuth telluride nanoribbons in this embodiment is 29 nm; the average length is 3.7 μm; The propylene glycol methyl ether acetate / N-methyl pyrrolidone mixed solvent of this embodiment is a mixture of propylene glycol methyl ether acetate and N-methyl pyrrolidone in a volume ratio of 34.5:65.5.
[0040] A method for preparing a graphene-based heating coating of this embodiment includes the following steps: S1. Add chloroform / propylene glycol methyl ether acetate mixed solvent, BYK-220S dispersant and silicone emulsion defoamer into a stirring tank, premix for 13 minutes at a stirring rate of 260 rpm, control the system temperature to maintain 25±5°C, then add functionalized graphene and surface-modified bismuth telluride nanoribbons, increase the stirring rate to 920 rpm and continue for 39 minutes to form a primary dispersed slurry; S2. polyaniline, bisphenol A epoxy acrylate and polyurethane acrylate were added to the primary dispersed slurry in sequence, and an ultrasonic probe was used to treat the slurry at a power of 160 W and a frequency of 26 kHz for 39 min, and the viscosity of the slurry was controlled to 2600 mPa·s at room temperature. Silane coupling agent KH560 was added, and the mixture was stirred at a rate of 590 rpm for 78 min under nitrogen protection to form a uniform composite slurry; S3. Add benzoin diethyl ether and HY-F-3777 fluorocarbon modified leveling agent to the composite slurry, mix at a stirring rate of 360 rpm for 26 min under light-proof conditions, and filter online through a microfiltration membrane with a pore size of 2.2 μm to remove aggregates to obtain a final coating slurry; S4. Apply the coating slurry on the surface of the substrate, transfer it to a UV curing device, irradiate it at a wavelength of 365nm and a light intensity of 65mW / cm² for 4.5min, control the substrate temperature at 49.5℃, and then post-cure it in a hot air circulation oven at 86℃ for 16min to form a graphene-based heating coating.
[0041] Example 3
[0042] A graphene-based heating coating is prepared from the following raw materials in parts by weight: 8 parts of functionalized graphene, 3.7 parts of surface-modified bismuth telluride nanoribbons, 6 parts of polyaniline, 26 parts of bisphenol A epoxy acrylate, 11 parts of polyurethane acrylate, 1.1 parts of benzoin diethyl ether, 1.4 parts of BYK-220S dispersant, 0.6 parts of HY-F-3777 fluorocarbon modified leveling agent, 1.9 parts of silane coupling agent kh560, 0.4 parts of silicone emulsion defoamer, and 34 parts of propylene glycol methyl ether acetate / N-methylpyrrolidone mixed solvent.
[0043] The preparation method of functionalized graphene is as follows: in parts by weight, hyperbranched polyolefin-acryl-POSS copolymer and graphene oxide are used as raw materials, mixed in a mass ratio of 1:5.2 and added into 92 mL of chloroform solvent to form a mixed system, the mixed system is placed in an ultrasonic treatment device, the ultrasonic power is controlled to be 304 W, the treatment time is 31 min, and the treatment temperature is maintained at 26° C., then the mixed system after ultrasonic treatment is transferred to a centrifuge, centrifuged at a speed of 5420 rpm for 46 min, unpeeled aggregates are removed, the supernatant is collected to obtain a graphene primary dispersion, the graphene primary dispersion is vacuum filtered through a polytetrafluoroethylene filter membrane with a pore size of 102 nm, and the sediment on the surface of the filter membrane is gradient washed with a chloroform solvent, 51 mL of solvent is added each time and washed at a stirring rate of 420 rpm for 5 min, the washing is repeated 4 times, and the purified functionalized graphene powder is dried in a vacuum environment at 53° C. for 20 h to obtain functionalized graphene.
[0044] The preparation method of the hyperbranched polyolefin-acryl-POSS copolymer is as follows: by weight, 100 parts of acrylic-cage polysilsesquioxane, 14.4 parts of 1,4-butanediol diacrylate and 102 parts of anhydrous dichloromethane are added to a Schlenk reaction bottle, the system temperature is controlled to be 31° C., and the mixture is stirred at a stirring rate of 420 rpm for 36 min to form a homogeneous solution, then 2.6 parts of α-diimide palladium by weight are dissolved in 52 parts of anhydrous dichloromethane, and the mixture is stirred at 0.8 mL / min via a syringe pump. The homogeneous solution was injected at a rate of n, the ethylene pressure was maintained at 0.10 MPa, and the polymerization was continuously stirred at 30°C for 24 hours. After the reaction, the solvent was removed by purging with nitrogen to obtain a preliminary product, which was then dissolved by adding 256 parts of tetrahydrofuran, and 1050 parts of methanol were added dropwise for precipitation. After filtration, the filter cake was washed three times with 400 parts of methanol, the product was redissolved in 210 parts of tetrahydrofuran, and 800 parts of acetone were added for secondary precipitation. The product was vacuum dried at 26°C for 72 hours to obtain a hyperbranched polyolefin-acryloyl-POSS copolymer.
[0045] The preparation method of surface modified bismuth telluride nanobelt is as follows: 100 parts of bismuth telluride nanobelt are weighed by weight, 380 parts of deionized water are added, and a uniform suspension is formed by dispersing for 48 minutes under the conditions of ultrasonic power of 220W and frequency of 38kHz; 14 parts of -aminopropyltriethoxysilane are added to the suspension, and the suspension is stirred for 2.2 hours at a magnetic stirring rate of 360rpm. After the reaction is completed, the suspension is centrifuged at 6000rpm for 16 minutes for solid-liquid separation, and the separated solid is repeatedly washed with 80 parts of deionized water for 3 times, each washing stirring rate is 320rpm, and the duration is 8 minutes; finally, the solid is placed in a vacuum drying oven, and dried for 9.6 hours at a temperature of 84°C and a vacuum degree of -0.092MPa, to obtain the surface modified bismuth telluride nanobelt.
[0046] The preparation method of bismuth telluride nanobelts is as follows: 10.1mmol bismuth chloride dihydrate, 15.1mmol tellurium powder, 80.4mmol potassium hydroxide and 30.2mmol potassium borohydride are mixed and transferred to a polytetrafluoroethylene-lined high-pressure reactor, and N,N-dimethylformamide is injected to 91wt.% of the volume of the reactor to form a precursor suspension; the sealed reactor is placed in a programmable oven, heated to 148°C at a heating rate of 3.8°C / min and kept at a constant temperature for 16 hours, and then naturally cooled to 31°C at a rate of 1.4°C / min; after opening the reactor, the reaction mixture is filtered through a Buchner funnel at a vacuum degree of -0.092MPa, and washed repeatedly with 80mL deionized water for 4 times, and then washed repeatedly with 42mL anhydrous ethanol for 3 times; finally, the product is dried at a temperature of 81°C and a vacuum degree of -0.092MPa for 10.4 hours to obtain bismuth telluride nanobelts.
[0047] The average width of the bismuth telluride nanoribbons in this embodiment is 38 nm; the average length is 6.4 μm; The propylene glycol methyl ether acetate / N-methyl pyrrolidone mixed solvent of the embodiment is a mixture of propylene glycol methyl ether acetate and N-methyl pyrrolidone in a volume ratio of 39:61.
[0048] A method for preparing a graphene-based heating coating of this embodiment includes the following steps: S1. Add chloroform / propylene glycol methyl ether acetate mixed solvent, BYK-220S dispersant and silicone emulsion defoamer into a stirring tank, premix for 16 minutes at a stirring rate of 320 rpm, control the system temperature to maintain 25±5°C, then add functionalized graphene and surface-modified bismuth telluride nanoribbons, increase the stirring rate to 1040 rpm and continue for 48 minutes to form a primary dispersed slurry; S2. polyaniline, bisphenol A epoxy acrylate and polyurethane acrylate were sequentially added to the primary dispersed slurry, and an ultrasonic probe was used to treat the slurry at a power of 220 W and a frequency of 32 kHz for 48 min, and the viscosity of the slurry was controlled to 3200 mPa·s at room temperature. Silane coupling agent KH560 was continuously added, and the mixture was stirred at a rate of 680 rpm for 96 min under nitrogen protection to form a uniform composite slurry; S3. Add benzoin diethyl ether and HY-F-3777 fluorocarbon modified leveling agent to the composite slurry, mix at a stirring rate of 420 rpm for 32 minutes under light-proof conditions, and filter online through a microfiltration membrane with a pore size of 3.4 μm to remove aggregates to obtain a final coating slurry; S4. The coating slurry was applied to the surface of the substrate, transferred to a UV curing device, irradiated for 6 minutes at a wavelength of 365 nm and a light intensity of 80 mW / cm², the substrate temperature was controlled at 54°C, and then post-cured in a hot air circulation oven at 92°C for 22 minutes to form a graphene-based heating coating.
[0049] Example 4
[0050] A graphene-based heating coating is prepared from the following raw materials in parts by weight: 12 parts of functionalized graphene, 4.5 parts of surface-modified bismuth telluride nanoribbons, 8 parts of polyaniline, 35 parts of bisphenol A epoxy acrylate, 15 parts of polyurethane acrylate, 1.5 parts of benzoin diethyl ether, 2.0 parts of BYK-220S dispersant, 0.8 parts of HY-F-3777 fluorocarbon modified leveling agent, 2.5 parts of silane coupling agent kh560, 0.5 parts of silicone emulsion defoamer, and 40 parts of propylene glycol methyl ether acetate / N-methylpyrrolidone mixed solvent.
[0051] The preparation method of functionalized graphene is as follows: in parts by weight, hyperbranched polyolefin-acryl-POSS copolymer and graphene oxide are used as raw materials, mixed in a mass ratio of 1:6 and added into 100 mL of chloroform solvent to form a mixed system, the mixed system is placed in an ultrasonic treatment device, the ultrasonic power is controlled to be 320 W, the treatment time is 35 min, and the treatment temperature is maintained at 30° C., then the mixed system after ultrasonic treatment is transferred to a centrifuge, centrifuged at a speed of 6500 rpm for 50 min, unpeeled aggregates are removed, the supernatant is collected to obtain a graphene primary dispersion, the graphene primary dispersion is vacuum filtered through a polytetrafluoroethylene filter membrane with a pore size of 110 nm, and the sediment on the surface of the filter membrane is gradient washed with a chloroform solvent, 55 mL of solvent is added each time and washed at a stirring rate of 500 rpm for 6 min, the washing is repeated 5 times, and the purified functionalized graphene powder is dried in a vacuum environment at 65° C. for 26 h to obtain functionalized graphene.
[0052] The preparation method of the hyperbranched polyolefin-acryl-POSS copolymer is as follows: by weight, 100 parts of acrylic-cage polysilsesquioxane, 16.0 parts of 1,4-butanediol diacrylate and 110 parts of anhydrous dichloromethane are added to a Schlenk reaction bottle, the system temperature is controlled to be 35° C., and the mixture is mixed at a stirring rate of 500 rpm for 40 minutes to form a homogeneous solution, then 2.8 parts of α-diimide palladium by weight are dissolved in 60 parts by weight of anhydrous dichloromethane, and the mixture is stirred at 1.0 mL / min via a syringe pump. The homogeneous solution was injected at a rate of 0.12 MPa while maintaining the ethylene pressure at 32°C for 26 h. After the reaction, the solvent was removed by nitrogen purging to obtain a preliminary product. 280 parts of tetrahydrofuran was added to dissolve the product. 1250 parts of methanol were added dropwise for precipitation. After filtration, the filter cake was washed three times with 500 parts of methanol. The product was redissolved in 250 parts of tetrahydrofuran. 1000 parts of acetone were added for secondary precipitation. The product was dried in vacuo at 30°C for 74 h to obtain a hyperbranched polyolefin-acryloyl-POSS copolymer.
[0053] The preparation method of surface modified bismuth telluride nanobelt is as follows: 100 parts of bismuth telluride nanobelt are weighed by weight, 500 parts of deionized water are added, and a uniform suspension is formed by dispersing for 60 minutes under the conditions of ultrasonic power of 300W and frequency of 40kHz; 20 parts of -aminopropyltriethoxysilane are added to the suspension, and the suspension is stirred for 3 hours at a magnetic stirring rate of 400rpm. After the reaction is completed, the suspension is centrifuged at 8000rpm for 20 minutes for solid-liquid separation, and the separated solid is repeatedly washed three times with 100 parts of deionized water in turn, and the stirring rate of each washing is 400rpm and the duration is 10 minutes; finally, the solid is placed in a vacuum drying oven, and dried for 12 hours at a temperature of 100°C and a vacuum degree of -0.10MPa, to obtain the surface modified bismuth telluride nanobelt.
[0054] The preparation method of bismuth telluride nanobelts is as follows: 10.5mmol bismuth chloride dihydrate, 15.5mmol tellurium powder, 82mmol potassium hydroxide and 31mmol potassium borohydride are mixed and transferred to a polytetrafluoroethylene-lined high-pressure reactor, and N,N-dimethylformamide is injected to 95wt.% of the volume of the reactor to form a precursor suspension; the sealed reactor is placed in a programmable oven, heated to 180℃ at a heating rate of 5℃ / min and kept at a constant temperature for 20h, and then naturally cooled to 35℃ at a rate of 2.0℃ / min; after opening the reactor, the reaction mixture is filtered through a Buchner funnel at a vacuum degree of -0.10MPa, and washed repeatedly with 100mL deionized water for 5 times, and then washed repeatedly with 50mL anhydrous ethanol for 3 times; finally, the product is dried at 85℃ and a vacuum degree of -0.10MPa for 12h to obtain bismuth telluride nanobelts.
[0055] The average width of the bismuth telluride nanoribbons in this embodiment is 50 nm; the average length is 10 μm; The propylene glycol methyl ether acetate / N-methyl pyrrolidone mixed solvent of this embodiment is a mixture of propylene glycol methyl ether acetate and N-methyl pyrrolidone in a volume ratio of 45:55.
[0056] A method for preparing a graphene-based heating coating of this embodiment includes the following steps: S1. Add chloroform / propylene glycol methyl ether acetate mixed solvent, BYK-220S dispersant and silicone emulsion defoamer into a stirring tank, premix for 20 min at a stirring rate of 400 rpm, control the system temperature to maintain 25±5°C, then add functionalized graphene and surface-modified bismuth telluride nanoribbons, increase the stirring rate to 1200 rpm and continue for 60 min to form a primary dispersed slurry; S2. polyaniline, bisphenol A epoxy acrylate and polyurethane acrylate were added to the primary dispersed slurry in sequence, and an ultrasonic probe was used to treat the slurry at a power of 300 W and a frequency of 40 kHz for 60 min, and the viscosity of the slurry was controlled to 4000 mPa·s at room temperature. Silane coupling agent KH560 was added, and the mixture was stirred at a rate of 800 rpm for 120 min under nitrogen protection to form a uniform composite slurry; S3. Add benzoin diethyl ether and HY-F-3777 fluorocarbon modified leveling agent to the composite slurry, mix at a stirring rate of 500 rpm for 40 min under light-proof conditions, and filter online through a microfiltration membrane with a pore size of 5 μm to remove aggregates to obtain a final coating slurry; S4. Apply the coating slurry on the surface of the substrate, transfer it to a UV curing device, irradiate it for 8 minutes at a wavelength of 365nm and a light intensity of 100mW / cm², control the substrate temperature at 60°C, and then post-cure it in a hot air circulation oven at 100°C for 30 minutes to form a graphene-based heating coating.
[0057] Comparative Example 1 It is basically the same as Example 1, except that the hyperbranched polyolefin-acryl-POSS copolymer is not used to functionalize the graphene, but the original graphene oxide is directly used.
[0058] Comparative Example 2 The method is substantially the same as Example 1, except that the bismuth telluride nanoribbons are not surface-modified with aminosilane.
[0059] Comparative Example 3 It is basically the same as Example 1, except that BYK-220S dispersant is not used.
[0060] Comparative Example 4 The method is substantially the same as Example 1, except that the silane coupling agent KH560 is not used.
[0061] Comparative Example 5 It is basically the same as Example 1, except that the illumination time of the UV curing stage is shortened to less than 1 min.
[0062] Comparative Example 6 The method is substantially the same as Example 1, except that the silicone emulsion defoamer is not used.
[0063] Comparative Example 7 It is basically the same as Example 1, except that BYK-220S dispersant is not used.
[0064] Comparative Example 8 It is basically the same as Example 1, except that functionalized graphene is not used.
[0065] Comparative Example 9 It is basically the same as Example 1, except that the surface-modified bismuth telluride nanobelt is not used.
[0066] Performance Testing: Adhesion test: Adopt ASTM D3359 standard and test the adhesion of coating by cross-cut method. Use multi-edge cutting blade to draw standard grid pattern on the coating surface, apply high-viscosity tape and tear it off quickly, observe the peeling of coating, and evaluate the adhesion according to standard grade. Higher adhesion indicates that the coating is firmly bonded to the substrate and is not easy to peel off.
[0067] Resistivity and Seebeck coefficient test: According to ASTM D257 standard, the volume resistivity and surface resistivity of the coating are measured by the four-probe method. Under a constant temperature and humidity environment, coatings of different thicknesses are tested and their conductivity is calculated to evaluate the effects of functionalized graphene and surface-modified bismuth telluride nanoribbons on the conductive network of the coating. The thermoelectric properties of the coating are determined using a Seebeck coefficient and conductivity simultaneous test system. The Seebeck coefficient is measured by setting a temperature difference (such as ΔT = 10K, 20K) in the room temperature to high temperature range (such as 25℃~300℃).
[0068] Heat stability test: According to ASTM D2485 standard, the coating sample is placed in a high-temperature oven and heated at a set temperature (such as 150℃, 200℃, 250℃) for a certain period of time (such as 24h or 48h). Then the changes in the coating appearance, including color, cracks, blistering and peeling, are observed to evaluate the thermal stability in a high temperature environment.
[0069] Thermal cycle test: According to IEC 60068-2-14 standard, the coating sample is cycled between -40℃ and 200℃ for a certain number of times (such as 500 cycles). Each cycle includes rapid heating, constant temperature holding, rapid cooling and constant temperature holding. The coating is observed to see if cracks, peeling or performance degradation occurs, so as to evaluate its thermal shock resistance.
[0070] The properties of the coatings of Examples 1 to 4 and Comparative Examples 1 to 9 are summarized in Table 1.
[0071] Table 1. Performance summary of coatings of Examples 1 to 4 and Comparative Examples 1 to 9
[0072] As can be seen from Table 1, the failure to use functionalized graphene will lead to the breakage of the conductive network, which will significantly increase the resistivity, while the Seebeck coefficient will decrease, and the adhesion will decrease, further affecting the heat resistance and thermal cycle performance, making the coating easy to fail. Unmodified bismuth telluride nanobelts will weaken the interfacial bonding force, causing the filler to be unevenly dispersed in the matrix, resulting in an increase in resistivity, a decrease in the Seebeck coefficient, and a decrease in heat resistance and thermal cycle stability, which will easily cause cracks or peeling. The failure to use a dispersant will cause the filler to agglomerate, making the conductive network uneven, thereby increasing the resistivity and reducing the Seebeck coefficient, while the adhesion will decrease, and the overall stability of the coating will deteriorate. The failure to use a silane coupling agent will further reduce the interfacial bonding force, resulting in a weak bond between the filler and the matrix, increasing the resistivity, decreasing the Seebeck coefficient, and weakening the heat resistance and thermal cycle performance, and the coating will easily peel or crack. Insufficient UV curing time will cause the crosslinking density to decrease, thereby affecting heat resistance and mechanical properties. Although the Seebeck coefficient is slightly lower, the short-term conductive performance is still close to the embodiment. If defoaming agent is not used, microporous defects will be formed inside the coating, and stress concentration will slightly reduce the adhesion. Although the short-term conductivity is not significantly affected, the long-term thermal cycle life is reduced. When functionalized graphene is not used, the conductive network is most severely damaged, the resistivity increases significantly, the Seebeck coefficient decreases significantly, and the heat resistance and thermal cycle performance are the worst. The coating is very prone to cracks and accelerates failure. If modified bismuth telluride nanobelts are not used, the interfacial bonding force will be reduced, making the filler easy to agglomerate in the matrix, resulting in increased resistivity and decreased Seebeck coefficient. At the same time, the heat resistance and thermal cycle performance are weakened, making the coating more prone to peeling or aging failure.
[0073] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that all equivalent structural changes made under the concept of the present invention and using the contents of the present invention specification and drawings should be covered within the scope of protection of the claims of the present invention.
Claims
1. A graphene-based heating coating, characterized in that: The invention is prepared from the following raw materials in parts by weight: 3-12 parts of functionalized graphene, 2.5-4.5 parts of surface-modified bismuth telluride nanobelts, 2-8 parts of polyaniline, 12-35 parts of bisphenol A epoxy acrylate, 5-15 parts of polyurethane acrylate, 0.5-1.5 parts of benzoin diethyl ether, 0.5-2.0 parts of BYK-220S dispersant, 0.3-0.8 parts of HY-F-3777 fluorocarbon modified leveling agent, 1.0-2.5 parts of silane coupling agent kh560, 0.2-0.5 parts of silicone emulsion defoamer, and 25-40 parts of propylene glycol methyl ether acetate / N-methylpyrrolidone mixed solvent.
2. A graphene-based heating coating according to claim 1, characterized in that: The functionalized graphene is prepared by mixing a hyperbranched polyolefin-acryl-POSS copolymer and graphene oxide in a chloroform solvent, and then subjected to ultrasonic stripping, centrifugal separation, vacuum filtration, gradient washing and vacuum drying. The hyperbranched polyolefin-acryl-POSS copolymer is prepared by catalytic polymerization, solvent precipitation, suction filtration and vacuum drying of acrylic-cage polysilsesquioxane, 1,4-butanediol diacrylate and anhydrous dichloromethane in a Schlenk reaction system; The surface modified bismuth telluride nanobelt is prepared by ultrasonically dispersing the bismuth telluride nanobelt in deionized water, adding aminopropyltriethoxysilane for surface modification, and then subjecting the nanobelt to magnetic stirring, centrifugal separation, deionized water washing and vacuum drying.
3. A graphene-based heating coating according to claim 1 or 2, characterized in that: The preparation method of the functionalized graphene is as follows: in parts by weight, a hyperbranched polyolefin-acryl-POSS copolymer and graphene oxide are used as raw materials, mixed in a mass ratio of 1: (4-6) and added to 80-100 mL of chloroform solvent to form a mixed system, the mixed system is placed in an ultrasonic treatment device, the ultrasonic power is controlled to be 280-320 W, the treatment time is 25-35 min, and the treatment temperature is maintained at 20-30 ° C, then the mixed system after ultrasonic treatment is transferred to a centrifuge, centrifuged at a speed of 3800-6500 rpm for 40-50 min, unpeeled aggregates are removed, and the supernatant is collected to obtain a graphene primary dispersion liquid, the graphene primary dispersion liquid is vacuum filtered through a polytetrafluoroethylene filter membrane with a pore size of 90-110 nm, and the sediment on the filter membrane surface is gradient washed with a chloroform solvent, 45-55 mL of solvent is added each time and the supernatant is centrifuged at 300-500 The mixture was washed at a stirring rate of rpm for 3 to 6 min, and the washing was repeated 3 to 5 times. The purified functionalized graphene powder was dried in a vacuum environment at 35 to 65 °C for 10 to 26 h to obtain functionalized graphene.
4. A graphene-based heating coating according to claim 3, characterized in that: The preparation method of the hyperbranched polyolefin-acryl-POSS copolymer is as follows: by weight, 100 parts of acrylic-cage polysilsesquioxane, 12.0-16.0 parts of 1,4-butanediol diacrylate and 90-110 parts of anhydrous dichloromethane are added to a Schlenk reaction bottle, the system temperature is controlled to be 25-35° C., and the mixture is mixed at a stirring rate of 300-500 rpm for 30-40 minutes to form a homogeneous solution, then 2.2-2.8 parts of α-diimide palladium by weight are dissolved in 40-60 parts of anhydrous dichloromethane, and the homogeneous solution is injected at a rate of 0.5-1.0 mL / min through a syringe pump, and the ethylene pressure is maintained at 0.08-0.12 MPa, continuously stir and polymerize at 28-32°C for 22-26h. After the reaction, nitrogen is used to purge and remove the solvent to obtain a preliminary product, which is then added with 220-280 parts of tetrahydrofuran to dissolve, and 750-1250 parts of methanol are added dropwise to precipitate. After suction filtration, the filter cake is washed 2-3 times with 250-500 parts of methanol, the product is redissolved in 150-250 parts of tetrahydrofuran, and 500-1000 parts of acetone are added to perform secondary precipitation. The product is vacuum dried at 20-30°C for 70-74h to obtain a hyperbranched polyolefin-acryloyl-POSS copolymer.
5. A graphene-based heating coating according to claim 1 or 2, characterized in that: The preparation method of the surface modified bismuth telluride nanobelt is as follows: weigh 100 parts of bismuth telluride nanobelt by weight, add 200-500 parts of deionized water, disperse for 30-60 minutes under the conditions of ultrasonic power of 100-300 W and frequency of 35-40 kHz to form a uniform suspension; add 5-20 parts of -aminopropyltriethoxysilane to the suspension, stir for 1-3 hours at a magnetic stirring rate of 300-400 rpm, after the reaction is completed, centrifuge the suspension at 3000-8000 rpm for 10-20 minutes to separate the solid from the liquid, and wash the separated solid with 50-100 parts of deionized water for 2-3 times, each washing stirring rate is 200-400 rpm, and the duration is 5-10 minutes; finally, place the solid in a vacuum drying oven, and dry it at a temperature of 60-100°C and a temperature of -0.08--0.10 MPa vacuum conditions for 6 to 12 hours to obtain surface-modified bismuth telluride nanobelts.
6. A graphene-based heating coating according to claim 5, characterized in that: The preparation method of the bismuth telluride nanobelt is as follows: 9.5-10.5 mmol bismuth chloride dihydrate, 14.5-15.5 mmol tellurium powder, 78-82 mmol potassium hydroxide and 29-31 mmol potassium borohydride are mixed and transferred to a polytetrafluoroethylene-lined high-pressure reactor, and N,N-dimethylformamide is injected to 85-95wt.% of the volume of the reactor to form a precursor suspension; the sealed reactor is placed in a programmable oven, heated to 100-180°C at a heating rate of 2-5°C / min and kept at a constant temperature for 10-20h, and then naturally cooled to 25-35°C at a rate of 0.5-2.0°C / min; after opening the reactor, the reaction mixture is filtered through a Buchner funnel at a vacuum degree of -0.08-0.10 MPa, and washed repeatedly with 50-100 mL of deionized water for 3-5 times, and then washed with 30-50 mL of deionized water for 3-5 times. mL of anhydrous ethanol was repeatedly washed 2 to 3 times; finally, the product was dried at 75 to 85°C and -0.08 to -0.10 MPa vacuum for 8 to 12 h to obtain bismuth telluride nanobelts.
7. A graphene-based heating coating according to claim 1, characterized in that: The average width of the bismuth telluride nanobelt is 20-50 nm, and the average length is 1-10 μm.
8. A graphene-based heating coating according to claim 1, characterized in that: The propylene glycol methyl ether acetate / N-methyl pyrrolidone mixed solvent is prepared by mixing propylene glycol methyl ether acetate and N-methyl pyrrolidone in a volume ratio of (30-45):(55-70).
9. A method for preparing a graphene-based heating coating according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1. Add propylene glycol methyl ether acetate / N-methyl pyrrolidone mixed solvent, BYK-220S dispersant and silicone emulsion defoamer into a stirring tank, premix for 10-20 min at a stirring rate of 200-400 rpm, control the system temperature to maintain 25±5°C, then add functionalized graphene and surface-modified bismuth telluride nanoribbons, increase the stirring rate to 800-1200 rpm and continue for 30-60 min to form a primary dispersed slurry; S2. polyaniline, bisphenol A epoxy acrylate and polyurethane acrylate were added to the primary dispersed slurry in sequence, and an ultrasonic probe was used to treat the slurry at a power of 100-300 W and a frequency of 20-40 kHz for 30-60 min, and the viscosity of the slurry was controlled to 2000-4000 mPa·s at room temperature. Silane coupling agent KH560 was added, and the mixture was stirred at a rate of 500-800 rpm for 60-120 min under nitrogen protection to form a uniform composite slurry; S3. Add benzoin diethyl ether and HY-F-3777 fluorocarbon modified leveling agent to the composite slurry, mix at a stirring rate of 300-500 rpm for 20-40 min under light-proof conditions, and filter online through a microfiltration membrane with a pore size of 1-5 μm to remove aggregates to obtain the final coating slurry; S4. Apply the coating slurry on the surface of the substrate, transfer it to a UV curing device, irradiate it at a wavelength of 365 nm and a light intensity of 50~100 mW / cm² for 3~8 minutes, control the substrate temperature at 45~60℃, and then post-cure it in a hot air circulation oven at 80~100℃ for 10~30 minutes to form a graphene-based heating coating.
10. Use of a graphene-based heating coating prepared by the preparation method according to any one of claims 1 to 8 or a graphene-based heating coating according to any one of claim 9 in a heating appliance.
Citation Information
Patent Citations
An electrically heated coating, an electrically heated skin, and an anti-icing and snow-proof system
CN112920704B
Preparation method of pH-regulated bismuth telluride nanowire
CN113697780A
POSS (Polyhedral Oligomeric Silsesquioxane)-based acryloyloxy hyperbranched polyethylene and application of POSS-based acryloyloxy hyperbranched polyethylene in graphene / carbon nanotube hybrid electric heating coating
CN115850608A
Graphene electrothermal composite coating and preparation method thereof, electrothermal composite film based on coating and application
CN118755381A
Cited By
High-performance PO composite film for OMR vacuum transfer printing and preparation method of high-performance PO composite film
CN120645573A
High-performance po composite film for omr vacuum transfer and preparation method thereof
CN120645573B
Transparent film with electromagnetic field shielding performance and preparation method thereof
CN120881964A
Preparation method of quick-drying road marking composition
CN121108865A
High-temperature-resistant material for coating wing surface of aircraft and preparation method of high-temperature-resistant material
CN121203541A